Pressure induced semimetal to metal transition in MoTe2-xSex and WTe2-xSex. (2021) - Pal, Debarati; Patil, Swapnil; Chatterji, Sandip
Abstract: Two-dimensional transition metal dichalcogenides (TMDCs) are an emerging class of materials that make them eligible for diverse applications. Moreover, the capability of tuning electronic properties under extreme conditions create rich physics and hold them as candidates for optoelectronics, spintronics and nanoelectronics. We executed density functional theory (DFT) to address the electronic properties of MoTe2-x Sex and WTe2-x Sex with x = 1 under pressure. Both the compounds reveal a semimetallic property at ambient pressure. The electronic character of the band structure and density of states (DOS) exhibit a metallic transition near 3 GPa for both the compounds MoTeSe and WTeSe. The present work depicts a pressure studies up to 10 GPa to explore the lattice parameters, volume changes and c/a anomaly. WTeSe shows a Dirac like dispersion without any band crossings along Z-U symmetry path.